Computer-aided tuberculosis detection in chest radiographs: a review - Nyein Naing, Wai Yan; Htike@Muhammad Yusof, Zaw Zaw; Khan, Sheroz; Shafie, Amir Akramin (Wireilla Scientific Publications, Australia, 2014)
Tuberculosis (TB) is very dangerous and rapidly spread disease in the world. In the investigating cases for suspected tuberculosis (TB), chest radiography is not only the key techniques of diagnosis based on the medical imaging but also the diagnostic radiology. So, Computer aided diagnosis (CAD) has been popular and many researchers are interested in this research areas and different approaches have been proposed for the TB detection and lung decease classification. In this paper, the medical background history of TB decease in chest X-rays and a survey of the various approaches in TB detection and classification are presented. The literature in the related methods is surveyed papers in this research area until now 2014.